Dysregulated calcium signaling in the aged macaque entorhinal cortex associated with tau hyperphosphorylation - Bathla, Shveta; Datta, Dibyadeep; Bolat, Dinara; Woo, Elizabeth; Duque, Alvaro; Arellano, Jon I.; Arnsten, Amy F. T.; Nairn, Angus C. (Frontiers in Aging Neuroscience, 2025)
IntroductionTau pathology in sporadic Alzheimer’s disease (AD) follows a distinct pattern, beginning in the entorhinal cortex (ERC) and spreading to interconnected brain regions. Early-stage tau pathology, characterized by soluble phosphorylated tau, is difficult to study in human brains post-mortem due to rapid dephosphorylation.MethodsRhesus macaques, which naturally develop age-related tau pathology resembling human AD, provide an ideal model for investigating early tau etiology. This study examines the molecular processes underlying tau pathology in the macaque ERC, focusing on calcium and inflammatory signaling pathways using biochemical and immunohistochemistry.ResultsOur findings reveal an age-related decrease in PDE4 phosphodiesterase that hydrolyzes cAMP and increases in calpain-2 and glutamate carboxypeptidase II that occur in parallel with early-stage tau hyperphosphorylation at multiple epitopes (pS214-tau, pT181-tau, pT217-tau).DiscussionThese findings suggest that dysregulated calcium signaling in ERC, beginning in middle-age, may prime tau for hyperphosphorylation, potentially driving the early stages of AD, advancing our understanding of how ERC vulnerabilities contribute to neurodegeneration in AD.